PENGARUH WORD OF MOUTH, BRAND IMAGE, DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN YAMAHA MIO (Studi pada Konsumen yang Membeli Yamaha Mio di PT. Yamaha Mataram Sakti Cabang Purworejo) - Novita Febrianti; widiartanto widiartanto (Universitas Diponegoro, 2018)
The development and competition of the motorcycle’s industry business is increasing rapidly. They compete in providing the best product’s quality to retain their customers. This research was conducted on PT. Yamaha Mataram Sakti Purworejo. From sales data of Yamaha Mio on PT. Yamaha Mataram Sakti Purworejo it can be found that there are fluctuations of sales. As a company that engaged in transportation sector, PT. Yamaha Mataram Sakti Purworejo must provide positive word of mouth to its customers to convince them that Yamaha Mio has good brand image so it can cultivate strong brand trust on consumers. This study aims to determine the effect of Word of Mouth (X1), Brand Image (X2), and Brand Trust (X3) on consumer purchasing decisions (Y) on PT. Yamaha Mataram Sakti Purworejo. Type of research that used is explanatory research with data collection methods using interviews and data collection tools using questionnaires with a sample of 100 respondents PT. Yamaha Mataram Sakti Purworejo customers using the Purposive Sampling method. The analysis technique used are validity test, reliability test, simple linear regression, multiple linear regression, t test, and F test with SPSS 21. From the result of research indicate that word of mouth have strong influence to purchasing decision equal to 54,1%, brand image have good influence to purchasing decision equal to 55,8%, while brand trust influence strong to decision of purchase equal to 68,9%. It shows that brand trust variable to purchase decision variable has higher influence than word of mouth and brand image. Researcher suggests to improve purchase decision is to improve the inovation of model’s product, to improve the difference of colour type, to improve good machine and fluel, to improve the accuration information of Yamaha Mio’s quality, to make strong promotion to target market in mass media and electronic media, and to improve the service quality of PT. Yamaha Mataram Sakti Purworejo.